THE PROFESSIONAL COMPETENCE OF THE JOURNALIST AND THE SKILLS THAT MEDIATE FROM THE COVERAGE OF NATURAL CATASTROPHES. TRAINING ACTIONS FOR IMPLEMENTATIO: La competencia profesional del periodista y las competencias que median desde la cobertura de catástrofes naturales. Acciones de entrenamiento para su implementación. - Salabarría Melián, Luis Antonio (2023)
The journalist who wants to be trained is one who is a human, sensitive professional, who apprehends and appropriates modes of action consistent with the praxis in which he or she operates, so that he or she can construct the praxis from a news activity that does not account for of sensationalism that trivializes information. In this sense, all of this, in symbiosis, means that in times of natural disasters, journalists use a more credible mode of action, based on observing what skills they mediate so that journalistic culture can focus on ethics (values-feelings). and cognitively (skills-capabilities), all of which enables-trains them, to carry out a more credible journalistic activity, tangible to human essences, and, so that the performance is cognitively and socially more comprehensive. In this case, to comply with this premise, the objective of this article is to propose some actions and competencies (probable list) that can intervene for the coverage of natural disasters, to optimize the journalist's performance.